2015
DOI: 10.1007/s12144-015-9315-0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Paternal and Maternal Psychological Control, Self-Esteem, and Indecisiveness across Adolescent Genders

Abstract: The purpose of this study was to examine the relationship among adolescents’ indecisiveness, adolescents’ self-esteem, and maternal and paternal psychological control by focusing on the differences in the relationship among these variables across adolescent genders. A total of 381 Italian adolescents (215 boys and 166 girls), aged from 13 to 17 years, completed self-report measures of parental psychological control, self-esteem and indecisiveness. Since previous studies have highlighted indirect relations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
1
12
0
3
Order By: Relevance
“…However, this is inconsistent with a study of Cascio et al . (). They found that the relationship between parental psychological control and adolescents’ self‐esteem differed in boys and girls.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, this is inconsistent with a study of Cascio et al . (). They found that the relationship between parental psychological control and adolescents’ self‐esteem differed in boys and girls.…”
Section: Discussionmentioning
confidence: 97%
“…Psychological control destructively damages adolescents' self-evaluative process (Padilla-Walker & Nelson, 2012;Wuyts, Vansteenkiste, Soenens & Assor, 2015). Under this control, they cannot trust their own abilities and uniqueness and are prone to negatively evaluate themselves (Cascio, Guzzo, Pace, Pace & Madonia, 2016). They then may experience more internalizing problems (B edard et al, 2014;Lee & Stone, 2012).…”
Section: Mediating Role Of Self-troublementioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, gives rise to a series of consequences including distorting the view of the situation, which may lead to incorrect decisions (Di Fabio and Blustein, 2010 ). In the same vein, Cascio et al ( 2016 ) highlight the role of parents in the development of adolescents' self-esteem and its correlation in decision-making performance. In this respect, their study observed that when families perform parenting styles based on confidence in their children's abilities, the children develop firm and secure self-esteem that allows them to make rational decisions.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by previous investigations in many cultural contexts (e.g., Laible and Carlo, 2004;Lan et al, 2019c), maternal-but not paternal control-is strongly related to students' adjustment at school. Likewise, maternal and paternal control are distinctly associated with students' adjustment across different domains (Cascio et al, 2016). Given this, future initiatives are recommended to address these concerns and further develop a more fine-grained understanding of the association between parental control and school adjustment.…”
Section: Limitationsmentioning
confidence: 99%